2019
DOI: 10.1039/c9ta05789g
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial engineering and optical coupling for multicolored semitransparent inverted organic photovoltaics with a record efficiency of over 12%

Abstract: Guided by finite-difference time-domain (FDTD) and optical transfer matrix formalism (TMF) simulation, the contradiction between PCE and AVT was solved, and multicolored ST-OSCs with record high efficiency were achieved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 46 publications
1
68
0
Order By: Relevance
“…Organic solar cells have a number of advantages compared to many of their inorganic counterparts, such as being lightweight, mechanically flexible and aesthetically appealing (e.g., because of their semitransparency), promising their application in multiple areas where conventional photovoltaics cannot be employed, for instance, as PV modules for smart windows, energy‐generating wallpapers and beyond . Encouragingly, the light power conversion efficiency (PCE) of organic solar cells is rapidly increasing, and the best laboratory devices have recently surpassed the 17% threshold .…”
Section: Introductionmentioning
confidence: 99%
“…Organic solar cells have a number of advantages compared to many of their inorganic counterparts, such as being lightweight, mechanically flexible and aesthetically appealing (e.g., because of their semitransparency), promising their application in multiple areas where conventional photovoltaics cannot be employed, for instance, as PV modules for smart windows, energy‐generating wallpapers and beyond . Encouragingly, the light power conversion efficiency (PCE) of organic solar cells is rapidly increasing, and the best laboratory devices have recently surpassed the 17% threshold .…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–6 ] Recently, the power conversion efficiency (PCE) of a single‐junction device based on binary photoactive layer system had surpassed the 15–16% boundaries for opaque OSCs and 11–12% boundaries for semitransparent OSCs (ST‐OSCs), all of which were fabricated on rigid glass substrates. [ 7–14 ] Though the PCE had increased remarkably on rigid glass substrates, development of OSCs on flexible substrates particularly for flexible ST‐OSCs still lagged behind. [ 15–18 ] To date, the highest reported PCE for flexible ST‐OSCs with average visible light transmittance (AVT) of over 20% was just over 10%.…”
Section: Figurementioning
confidence: 99%
“…To realize semitransparency in OPVs and PSCs, one can manipulate the coverage, [ 35–43,161–163 ] thickness, [ 10–17,44–48,164,165 ] or bandgap of the active layer [ 2,8,9,18–24,49,50,166–168 ] or replace the opaque metal electrode with light‐transmitting media (e.g., metal nanowires, [ 44,46,51–56,169–171 ] transparent conducting oxides, [ 43,57–61,167,168,172–180 ] transparent conducting polymers, [ 40,62,63,181–184 ] graphene, [ 54,64,164,185 ] and carbon nanotube [ 65,186–188 ] ). Although the most convenient way to fabricate an ST‐PV is to decrease the thickness of the top metal electrode and, thereby, increase its transparency, [ 35,39,40,47,58,66–72,124 ] there is always a trade‐off between conductivity and transparency.…”
Section: Semitransparent Opvs and Pscsmentioning
confidence: 99%
“…[ 10–17 ] The integration of new structures with low‐bandgap active layer materials has provided high‐performance visibly transparent OPVs. [ 18–24 ] For instance, Yang et al demonstrated an ST‐OPV having a PCE of 12% and an average visible transmittance (AVT) of 20% using a thin Au/Ag electrode and a strategy of transparent hole‐transporting frameworks. [ 25 ] Several light‐trapping methods, including the incorporation of antireflection layers, [ 26,27 ] microcavity (MC) structures, [ 28 ] distributed Bragg reflectors (DBRs) and photonic crystals (PCs), [ 29,30 ] and nanostructures, [ 31,32 ] have further optimized the light harvesting and optical responses of such devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation